2017
DOI: 10.1101/209023
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Non-B-form DNA structures mark centromeres

Abstract: Animal and plant centromeres are embedded in repetitive "satellite" DNA, but are thought to be epigenetically specified. To define genetic characteristics of centromeres, we surveyed satellite DNA from diverse eukaryotes and identified variation in <10-bp dyad symmetries predicted to adopt non-Bform conformations. Organisms lacking centromeric dyad symmetries had binding sites for sequencespecific DNA binding proteins with DNA bending activity. For example, human and mouse centromeres are depleted for dyad sym… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 96 publications
0
1
0
Order By: Relevance
“…Recent studies on the architecture of centromeres have reported the presence of specific secondary structures such as DNA loops suggesting that active centromeric sequences were selected for their ability to form secondary structures, rather than for the nucleotide sequence itself (Aze et al. 2016; Kasinathan and Henikoff 2017). In fact, a bioinformatic analysis on the prediction of secondary structures showed that SAT1.723 can indeed form DNA loops and G-quadruplexes (data not shown; see Kejnovsky et al.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies on the architecture of centromeres have reported the presence of specific secondary structures such as DNA loops suggesting that active centromeric sequences were selected for their ability to form secondary structures, rather than for the nucleotide sequence itself (Aze et al. 2016; Kasinathan and Henikoff 2017). In fact, a bioinformatic analysis on the prediction of secondary structures showed that SAT1.723 can indeed form DNA loops and G-quadruplexes (data not shown; see Kejnovsky et al.…”
Section: Discussionmentioning
confidence: 99%